Low Doses of Glyphosate/Roundup Alter Blood–Testis Barrier Integrity in Juvenile Rats - Gorga, Agostina; Rindone, Gustavo Marcelo; Centola, Cecilia Lucía; Sobarzo, Cristian M.; Pellizzari, Eliana Herminia; Camberos, María del Carmen; Marín-Briggiler, Clara Isabel; Cohen, Debora J.; Riera, Maria Fernanda; Galardo, Maria Noel; Meroni, Silvina Beatriz (Frontiers in Endocrinology, 2021)
IIt has been postulated that glyphosate (G) or its commercial formulation Roundup (R) might lead to male fertility impairment. In this study, we investigated possible effects of G or R treatment of juvenile male rats on blood-testis barrier function and on adult male sperm production. Pups were randomly assigned to the following groups: control (C), receiving water; G2 and G50 , receiving 2 and 50 mg/kg/day G respectively; and R2 and R50 receiving 2 and 50 mg/kg/day R respectively. Treatments were performed orally from postnatal day (PND) 14 to 30, period of life that is essential to complete a functional blood-testis barrier. Evaluation was done on PND 31. No differences in body and testis weight were observed between groups. Testis histological analysis showed disorganized seminiferous epithelium, with apparent low cellular adhesion in treated animals. Blood-testis barrier permeability to a biotin tracer was examined. A significant increase in permeable tubules was observed in treated groups. To evaluate possible mechanisms that could explain blood-testis barrier permeability, intratesticular testosterone levels, androgen receptor expression, thiobarbituric acid reactive substances and the expression of intercellular junction proteins (claudin11, occludin, ZO-1, connexin43, 46 and 50) were examined. No modifications in the above-mentioned parameters were detected. To evaluate whether juvenile exposure to G and R could have consequences during adulthood, a set of animals of the R50 group was allowed to grow up until PND 90. Histological analysis showed that control and R50 groups had normal cellular associations and complete spermatogenesis. Also, blood-testis barrier function was recovered and testicular weight, daily sperm production and epididymal sperm motility and morphology did not seem to be modified by juvenile treatment. In conclusion, the results show that continuous exposure to low doses of G or R alters blood-testis barrier permeability in juvenile rats. However, considering that adult animals treated during the juvenile stage showed no differences in daily sperm production compared with control animals, it is feasible to think that blood-testis barrier impairment is a reversible phenomenon. More studies are needed to determine possible damage in the reproductive function of human juvenile populations exposed to low doses of G or R.